Efektivitas Program Pekarangan Pangan Lestari di Kabupaten Lombok Timur (Jurnal Insan Pendidikan dan Sosial Humaniora, 2025)
The Sustainable Food Yard Program (P2L) is the government's effort to increase community food security through the use of home yards. In the Barokah Women Farmers Group (KWT), Majidi Village, Selong District, East Lombok Regency, this program was implemented with the aim of empowering women farmers in managing their yards to be more productive and support family food security. However, in its implementation, this program faces various challenges that affect its effectiveness. This study aims to analyze the effectiveness of the P2L Program at KWT Barokah, as well as identify the supporting and inhibiting factors that affect the implementation of the program. The research method used is qualitative descriptive with data collection techniques including interviews, observations, document collection, and review of previous research. The data obtained were then analyzed using the Miles and Huberman data analysis model, resulting in findings that were in accordance with the focus of the research. The results of the study show that the Sustainable Food Yard Program at KWT Barokah has good productivity potential, as seen from the increase in the quantity of crops. However, this program still faces several obstacles, especially related to the lack of facilities and infrastructure as well as cultivation methods that are not optimal. In addition, limitations in storage facilities and cultivation techniques also affect the quality of production products. Therefore, significant improvements are needed in terms of facilities, infrastructure, and improving the skills of members to achieve optimal effectiveness.